1998
DOI: 10.1007/bf02783340
|View full text |Cite
|
Sign up to set email alerts
|

Trace element correlations in the blood of indian women with breast cancer

Abstract: Fourteen minor (Na, K, P, Fe) and trace (Br, Co, Cr, Cs, Hg, Rb, Sb, Se, Sr, Zn) elements have been determined in pre- and postoperative blood samples of 10 breast-cancer-affected. Indian women and compared with controls. The study showed elevation of Cr, Hg, Fe, Rb, Sb, and Zn and lowering of Se, K, P, and Sr contents in the blood of cancer patients. Most elemental contents in pre- and postoperative stages remain unaltered except Br, Co, and Sb. Statistical significance of Fe, Se, Zn, and Hg levels has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…Similarly, higher Pb contents in dietary intake were linked with the cancers of stomach, small intestine, large intestine, ovary, kidney, lung, myeloma, all lymphorms and all leukemia (Hayes 1997;Fanning 1988;Selevan et al 1996;Schrauzer et al 1977). Significant correlations have been reported between blood Cr and Zn levels and mortalities from cancers of breast, colon, rectum, ovary, lung, pancreas, leukemia and bladder (Hayes 1997;Schrauzer 2000;Singh and Garg 1998;Davies 1984;Robinson et al 1973). Association of Cr intake with respiratory, lung and nasal cancers has also been reported (Langard and Vigander 1983;Hayes et al 1989;Davies et al 1991).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Similarly, higher Pb contents in dietary intake were linked with the cancers of stomach, small intestine, large intestine, ovary, kidney, lung, myeloma, all lymphorms and all leukemia (Hayes 1997;Fanning 1988;Selevan et al 1996;Schrauzer et al 1977). Significant correlations have been reported between blood Cr and Zn levels and mortalities from cancers of breast, colon, rectum, ovary, lung, pancreas, leukemia and bladder (Hayes 1997;Schrauzer 2000;Singh and Garg 1998;Davies 1984;Robinson et al 1973). Association of Cr intake with respiratory, lung and nasal cancers has also been reported (Langard and Vigander 1983;Hayes et al 1989;Davies et al 1991).…”
Section: Resultsmentioning
confidence: 85%
“…Significantly higher Cr and Zn levels and lower levels of Cu were reported in the scalp hair of patients with malignant tumours than in the scalp hair of healthy donors (Kolmogorov et al 2000), evidencing that higher hair Cr and Zn contents indicated increased cancer risk. Moreover, Cr and Zn had been reported to be significantly higher in the blood of breast cancer patients as compared with healthy donors (Singh and Garg 1998), and had been significant experimental evidence that Cr stimulate oxygen radical production which induces DNA damage (Clodfelder et al 2004). Breast cancer mortality was found to be strongly contributed by Cr, followed by Cd and Zn, while for prostate cancer, Cd revealed the strongest contribution followed by Zn and Cr (Hayes 1997;Drasch et al 2005;Schrauzer 2006).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Significantly higher Cr levels have recently been observed in the blood of Indian breast cancer patients as compared with healthy controls [90]. In these patients, blood Zn and Hg concentrations were also elevated, and blood Se and Hg were directly correlated (P B 0.05), indicating an interaction between the two elements.…”
Section: Multiple Elementsmentioning
confidence: 84%
“…It will be possible for us to develop new therapeutically strategies aimed at target molecules as we obtain more information on multi-stage cancer growth. Given the worldwide prevalence of the disease, defining the molecular determinants to identify individuals that might be at risk has become an emergency requirement [5][6][7]. Since the 1970s, evidences that trace elements are essential for the body to maintain its natural balance have caused this subject to become attractive.…”
Section: Discussionmentioning
confidence: 99%